2016
DOI: 10.1371/journal.pone.0155154
|View full text |Cite
|
Sign up to set email alerts
|

Repeated and Widespread Evolution of Bioluminescence in Marine Fishes

Abstract: Bioluminescence is primarily a marine phenomenon with 80% of metazoan bioluminescent genera occurring in the world’s oceans. Here we show that bioluminescence has evolved repeatedly and is phylogenetically widespread across ray-finned fishes. We recover 27 independent evolutionary events of bioluminescence, all among marine fish lineages. This finding indicates that bioluminescence has evolved many more times than previously hypothesized across fishes and the tree of life. Our exploration of the macroevolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
168
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(178 citation statements)
references
References 37 publications
5
168
1
4
Order By: Relevance
“…It is indeed an important and rather common evolutionary phenomenom, which may involve all kinds of traits, including behavioural, morphological, developmental, and molecular ones. (Davis, Sparks, & Smith, ; Friedman, Price, Hoey, & Wainwright, ; Gallant et al., ; Losos, ; Losos, Jackman, Larson, de Queiroz, & Rodriguez‐Schettino, ; Mahler, Ingram, Revell, & Losos, ; Pfenning et al., ; Ujvari et al., ; Vidal‐García & Keogh, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is indeed an important and rather common evolutionary phenomenom, which may involve all kinds of traits, including behavioural, morphological, developmental, and molecular ones. (Davis, Sparks, & Smith, ; Friedman, Price, Hoey, & Wainwright, ; Gallant et al., ; Losos, ; Losos, Jackman, Larson, de Queiroz, & Rodriguez‐Schettino, ; Mahler, Ingram, Revell, & Losos, ; Pfenning et al., ; Ujvari et al., ; Vidal‐García & Keogh, ).…”
Section: Introductionmentioning
confidence: 99%
“…It was known that bioluminescence has evolved independently more than 40 times, with males often using it as a mating signal but with also some other possible adaptive functions including anti-predator defense and predation. Moreover, it has been reported that small marine lanternfishes and sharks that use bioluminescence in mate identification had a greater concentration of species than other deep-sea fishes that use bioluminescence for defensive purposes [2][3][4]. But no one had ever determined whether this pattern is consistent across diverse and distantly related animal groups living on sea and land.…”
mentioning
confidence: 99%
“…Although, this possibility might at first sight appear remote, endosymbiotic bacteria fulfil many functions in vertebrates, including the production of bioluminescence in many deep sea fish18. Such bacterially mediated bioluminescent symbiosis has evolved at least 27 times across diverse orders of ray-finned fishes19, indicating the scope for the evolution of such prokaryote/eukaryote relationships. A third, less likely, possibility is that the photosensitizer is manufactured by Malacosteus itself with appropriate genes being incorporated into the animal’s genome, potentially by horizontal gene transfer from prokaryotes.…”
mentioning
confidence: 99%